Indigenous Corporations and the Best Interests of the Corporation: Members or Beyond? - Nehme, Marina (Victoria University of Wellington Law Review, 2025)
Directors of Indigenous corporations registered under the Corporations (Aboriginal and Torres Strait Islander) Act 2006 (Cth) (CATSI Act) and directors of companies registered under the Corporations Act 2001 (Cth) have similar duties. However, the context in which these legal entities operate is different, with Indigenous corporations mainly operating in the not-for-profit sector supplying essential services to their communities. Additionally, these corporations are established under legislation designed to be "a special statute of incorporation for Aboriginal and Torres Strait Islander peoples that takes account of the special risks and requirements of the Indigenous corporate sector". Accordingly, this article considers the extent to which the best interests obligation imposed on directors under s 265-5 of the CATSI legislation goes beyond the interest of members to take into account the interest of the stakeholders. In doing this, the article first reviews the interpretation of the sister provision of s 265-5 in the Corporations Act to understand how the provision operates and the implications of such an interpretation on the management of Indigenous corporations. Further, the article analyses the role that members and stakeholders play in the Indigenous corporation and then assesses possible avenues that may be available to ensure that this directors’ duty is in line with the core purpose of the CATSI Act.